Réponses

2012-10-24T18:27:52+02:00

A = 2(4x+5) +(5x+7) -3(9+5x)

A = 8x + 10 + 5x +7 -27 -15x

A = 13x +17 -27 -15x

A = -2x -10

 

Pour le reste c'est pareil, tu applique les regles de multiplication et n'oublie pas de ne pas mélanger les nombres

 

Au plaisir

2012-10-24T18:34:53+02:00

A=2(4x-5)+(5x+7)-3(9+5x)=8x-10+5x+7-27-15x=-2x-30

B=9(x-8)-(x²-3x)-7(x-9)=9x-72-x²+3x-7x+63=-x²+5x-9

C=-3(1+4x)-4(5x+8)+x(4x-7)=3+12x-20x-32+4x²-7x=4x²-15x-32

D=-5(-1+3x²)-x(5+x)-2(3-2x)=5-15x²-5x-x²-6+4x=-16x²-x-1